Research on Online Monitoring System for Oil Formation Parameters - Fan, Wu; Zhang, Qizhi; Qin, Winhao (International Journal of Natural Resources and Environmental Studies, 2024)
China is in the stage of rising water content in crude oil reservoirs, and the water content, temperature and pressure of the oil layer will have a significant impact on the efficiency of crude oil extraction. After adopting the layered injection technology, the contradiction between layers has been improved to a certain extent, but there are differences in the permeability of each oil layer, and the water injected into the oil layer with better permeability is single-layer surging, which leads to the increase of water content of the extracted fluid. Aiming at this problem, this study is devoted to designing a set of digital oil reservoir monitoring device, which can detect and analyze the water content, temperature and pressure parameters of each reservoir in real time, and then carry out systematic exploitation for different oil reservoir states. Through model simulation, hardware design, software development, and sensor production and improvement, a complete downhole oil formation structure model is built to simulate the real oil extraction process. The device utilizes electromagnetic conductivity method to design and produce a highly reliable water content sensor, combined with temperature and pressure sensors and filtering algorithms for parameter compensation, the measured data are collected and processed by microcontroller, and the interaction between microcontroller and host computer software is established by serial communication. PC adopts VOFA+ host computer to build a complete set of simulated oil extraction system with hand-automated integrated control and display interface.